Grain diffusion and dispersion properties of clayey soils taken from Bogacay Antalya - Mahmutoğlu, Barış; Tekinsoy, Mehmet Arslan (PAMUKKALE UNIV, 2016)
As clayey soils get compressed, settled and reach to a more compact state by means of consolidation, they are subjected to grain diffusion and dispersion. Considering this phenomenon, information can he obtained on both settlement properties und time rates of settlement of soils. Percentages of dry unit weight variations before and after a consolidation process und plasticity properties olsoils appear to be two important aspects M dispersion and g ruin diffusion. In this study, clayey soils obtained from Bogacay Antalya are evaluated in terms of grain diffusion and dispersion by means of performing consolidation tests. Obtained results of the experiments are compared to theoretical counterparts and related comments ure given. By that means, diffusive and dispersive characteristic of the region in a consolidation process is defined.
Keywords: Dispersion; Grain diffusion; Time rates of settlement; Dry unit weight; Plasticity